Citra Perempuan dalam Novel Gadis Minimarket Karya Sayaka Murata: Kritik Sastra Feminisme - Purba, Wahibah Nabila (Medan Resource Center, 2023)
This research aims to describe the image of women in the novel Minimarket Girl by Sayaka Murata which is studied from its physical, psychological and social aspects. This research is a type of qualitative descriptive research. Her character in the minimarket girl novel considers herself normal but not from the perspective of the people around her. Therefore, he felt comfortable working in a convenience store which he thought could make him feel normal. Because the depiction of the story in the novel Minimarket Girl by Sayaka Murata is felt to be quite close to the reality of life in Japan. Therefore, the author chose the novel Minimarket Girl to be the object of research. Based on the explanation explained above, the author will examine the image of women in the novel Minimarket Girl by Sayaka Murata through a feminist literary criticism approach.